(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
Palimpsestes dealt with expectations of the theory of the cinema. However, the new post- modern terminological uses overshadowed the definitions, stemming from the poetics, by opening up these categories of references and by devoting a large part to the affective colour, such as irony or neutrality. The problem is that these affective colours prove subjective and correspond to the particular phenomena of reception. On the contrary, the approach of Genette about parody and pastiche film contributes to a better understanding of these phe- nomena. In this paper, I suggest that this understanding requires an adaptation to the speci- ficity of the cinematic medium.